Olfaction Ecology of Peak Cudding in Similipal Tigers - Choudhury, Saroj Raj (Indian Forester, 1977)
An intensive, round the clock, in vivo study of a tame hut free living female tiger (Panthera tigris), Khairi, is being conducted by me since nearly three years. Retro-extrapolation of her growth graph places her date of birth on August 5, 1974. The day she came from the Similipal forests, she was two months old (Plate I). Measurements lay stress on physiology and behaviour. Significant, related data in interpreted for specific ecological meaning. Olfaction vis-a-vis peak cubbing season is one such.